PATHOLOGY OF MELOXICAM TOXICITY IN COCKEREL BIRDS - Hedau, Madhuri; Bhadarkar, AG (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
An experiment was conducted to study meloxicam toxicity in poultry. Toxicity was induced by oral administration of meloxicam to groups B, C and D @ 0.2, 0.4 and 0.8 mg/kg body weight respectively and group A served as a control. Haematological and biochemical parameters were studied at 0, 8, 24, 48 and 72 hrs of experiment. The observations revealed decrease in Hb, PCV, TEC along with leucocytosis and absolute heterophillia in groups C and D. Serum uric acid, creatinine, AST and ALT values were found elevated in groups C and D. The serum biochemical deviations in the present study indicated nephrotoxic and hepatotoxic effects of meloxicam in poultry at higher doses of the drug.
Keywords: Cockerels; meloxicam; toxicity; Haematobiochemical